Ketika Startup Gagal: Analisis Red flags untuk Membedakan Business Failure, Governance Failure, dan Fraud Risk pada TaniHub, Investree, dan eFishery - Ari Utomo Saputra; Ari Ayu; Anisatun Humayrah Rais; Hasma Hasma; La Ode Abdul Rakhman (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study analyzes red flags in failed Indonesian startups and maps the characteristics of business failure, governance failure, and fraud risk in the context of venture capital funding. Using a multi-case study (Yin, 2018), the study examines TaniHub, Investree, and eFishery to identify their respective failure patterns. The results indicate that TaniHub experienced business failure due to premature expansion, excessive growth ambition, high burn rate, and cash flow anomalies. Investree experienced governance failure due to weak board oversight, internal controls, and post-investment monitoring. Meanwhile, eFishery indicated fraud risk triggered by founder dominance, founder-friendly governance, revenue quality issues, data inconsistencies, and failed investor verification. The cross-case analysis revealed systemic weaknesses in the form of ineffective monitoring, inadequate due diligence, and delayed response. Based on these findings, a Startup Failure Framework was developed that integrates Agency Theory, information asymmetry, red flags, and due diligence. This framework demonstrates that agency conflicts do not always lead to fraud but instead produce three different outcomes depending on the configuration of red flags and the effectiveness of oversight. This research contributes to expanding the venture capital governance literature across a single risk spectrum.